Literature in the home - Romick, Winnie Luella (My University, 1894)
Introduction: Home: What pleasant thoughts are connected with this simple little word. It constitutes the circle within which we turn for comfort and solace after our daily labors or weary wanderings. It is the place we will in later years enjoy looking back upon as the pride of our childhood days. It calls to our minds the fond memories of old associates and will always be the dearest spot on earth “Be it ever so humble”. A few years ago Jennie Lind, the renowned songstress, who was singing before an audience in New York did not touch the very hearts of the people until she began to pour forth “Home Sweet Home”. The audience gave way to their feelings at once and thousands were seen with tears gushing from their eyes. Someone has said, “Next to religion, the deepest and most ineradicable sentiment in the human soul is that of the home affections. “There cannot be any real happiness in life or no misery without the home and this home is what we make it. Of the parents are kind and always ready to give their good advice, brothers and sisters always ready to share each other’s joys and sorrows, then the home will be a place of peace and happiness. It surely will be a blessing to the parents if this child is started on the right road to win for himself friends, success, or, best of all, eternal life. He will be the pride of his parents and a joy to his friends.
Citation: Romick, Winnie Luella. Literature in the home. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Home; Literature; Childhood; Development; Education; Theses; Manuscripts (documents)